ONLINE OFFLINE LANGUAGE LEARNING: BASED ON INDONESIAN STUDENTS’ PERPECTIVE (EXPERIENCE OR ENGAGEMENT) AT STKIP MUHAMMADIYAH SUNGAI PENUH - Ria Agustina; Mufida Maryamah Gusti; Yoga Karmizi (EDU RESEARCH, 2024)
This research aimed to investigate the Indonesian Study Program students’ perpective (experience or engagament) toward the online offline language learning st STKIP Sungai Penuh. This was a descriptive qualitative study. The respondents of this research were 30 student at Indonesian Study Program at STKIP Sungai Penuh. The instrument of this reserach was an inteview. The interview guideline was designed by the theory from Trowler (2010) and Fredricks et al (2004) who divided three indicators of stduents’ engagement criteria, namely; behavioral, emotional, and cognitive. This research found that mostly the students have good experience and feelings while learning language in offline rather than in online class. The students have a big eager to participate language class in offline learning rather than online. They said that in language class, they always actively participate in class, whether responding to the lecturer's questions or making presentations in class. Mostly the students answered it was easy or not too difficult to complete the task while studying language in offline learning. And also the students feel excitement and challenging while studying language in offline class rather than online.